Criminality and Economic Disparity in Indonesia Post-Pandemic - Hyogatama, Iqbal Halilintar; Adiwibowo, Tezar Maulana; Mulya, Hezkiel Krisna; Pratiwi, Mulia Kharisma; Pangestuti, Rinda Siaga; Khatimah, Husnul (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research investigates the relationship between economic factors and incidences of sexual harassment and violence, highlighting the potential repercussions of economic downturns on crime rates. It emphasizes the necessity of economic sector enhancement, bolstered by skilled human resources, to mitigate these issues and foster job creation. Method: The study employs community service activities to reduce violence and enhance human resources, particularly in barista skills. Utilizing socialization and training techniques, it examines the impact of marketing psychology on identifying market opportunities for community economic development. Practical Applications: The findings offer insights into addressing social issues through economic empowerment, enhancing employability skills, and fostering community economic growth. Implementing these strategies can contribute to crime prevention and socioeconomic advancement. Conclusion: Economic stability and skill development are crucial in combating violence and promoting community welfare. This research underscores the significance of integrating economic initiatives with social interventions to address multifaceted societal challenges effectively.